2006
DOI: 10.1002/eji.200636602
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of leptin signaling in the survival and maturation of bone marrow‐derived dendritic cells

Abstract: Previous studies demonstrated that lymphocyte development is impaired in leptin receptor (Ob-R)-deficient db/db mice. However, it remains unclear whether or not leptin signaling plays a physiological role in dendritic cell (DC) development and function. In this study, we first detected Ob-R expression in murine DC. Using db/db mice at a pre-diabetic stage, we demonstrate that the total number of DC generated from bone marrow (BM) cultures is significantly lower than in WT controls. Similarly, selective blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
81
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 49 publications
12
81
0
5
Order By: Relevance
“…Leptin activates NF-kB in dendritic cells, whereas a leptinsignaling deficiency leads to enhanced levels of the inhibitor protein of NF-kB ( Figure 2). 37 The above-described role of leptin in the function of the immune system could be relevant in both cellular and humoral immunity.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 204mentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin activates NF-kB in dendritic cells, whereas a leptinsignaling deficiency leads to enhanced levels of the inhibitor protein of NF-kB ( Figure 2). 37 The above-described role of leptin in the function of the immune system could be relevant in both cellular and humoral immunity.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 204mentioning
confidence: 99%
“…24,36 In fact, leptin receptors can also be found in different tissues and immune cell types, including various subpopulations of T and B lymphocytes, dendritic cells, monocytes, neutrophils, macrophages and natural killer (NK) cells. 18,[37][38][39][40][41] The cytokine-like structural characteristic of leptin is implicative of its function in regulating immune responses. This concept is discussed in detail in the present review.…”
Section: Introductionmentioning
confidence: 99%
“…This report demonstrated that human DC express functional leptin receptors and that leptin promotes differentiation of peripheral bloodderived DC, protects them from apoptosis, modulates cytokine production, and -quite importantly -licenses them for Th1 priming of CD4 + T cells [13]. In this issue of the European Journal of Immunology, Lam et al [14] describe for the first time the effect of leptin receptor deficiency on DC survival, maturation and function in mice. This report by Lam et al [14]describes how murine bone marrow-derived DC express functional leptin receptors and respond to leptin stimulation with activation of the JAK2 pathway.…”
mentioning
confidence: 95%
“…Despite the fact that Mattioli et al [13] and Lam et al [14] evaluated the effect of leptin in DC using two different organisms (human and mouse respectively) and from two opposite experimental perspectives (the addition of leptin in the study by Mattioli et al [13], leptin receptor-deficiency/blockade in Lam et al [14]), the pattern of the findings is astoundingly similar: in both systems, leptin protects DC from apoptosis, induces DC maturation, upregulates production of TNF-a and IL-12 while downregulating IL-10 synthesis, and increases the ability of DC to stimulate CD4 + lymphocytes. The only major difference observed between the two reports concerns the effect of leptin on the expression of co-stimulatory molecules by DC, an effect which was present in the report by Lam et al [14] but absent in that of Mattioli et al [13].…”
mentioning
confidence: 98%
See 1 more Smart Citation